The nuclear condition in the twenty-first century: Techno-political aspects in historical and contemporary perspectives. (October 2019) - Beardsworth, Richard; Behr, Hartmut; Luke, Timothy W
This Introduction presents the seven closely interlinked papers that explore the theme of this Special Issue, and one of the enduring existential questions for International Relations: the nuclear condition in the twenty-first century. The Special Issue is the second to come from two workshops sponsored by a UK Leverhulme grant, and it builds upon the first, more theoretical Special Issue, which brought Classical Realist and Critical Theory texts into dialogue. The major concern in the first Special Issue—the focus on modernity, crises, and humanity—is taken up here in more grounded practical terms, framed around the existential fears of nuclear annihilation. Each of the contributions re-assess the contemporary nuclear condition from within the theoretical frameworks provided by Classical Realism and Critical Theory. The engagement with both traditions allows the contributors to diagnose what is new, and what remains constant, in the contemporary nuclear condition.